Why Handshakes Persist: Understanding the Influence of Beliefs on the Socializing Decisions of Young People During COVID-19 in Nigeria - Nche, George C. (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Despite the global shift toward contactless greetings prompted by the COVID-19 pandemic, a substantial number of young people in Nigeria continue to engage in the practice of shaking hands. Previous empirical studies on COVID-19 and handshakes have primarily focused on adherence rates in different countries, with limited attention to understanding the underlying beliefs influencing adherence or non-adherence to preventive measures. This study explored the underlying beliefs that inform these socializing choices, shedding light on the socio-cultural and psychological factors affecting adherence to this age-old practice. Data were collected from twelve participants through in-depth interviews and analyzed thematically using a descriptive-analytical approach. The findings indicate that participants often feel immune to COVID-19, attributing this immunity to self-administered hydroxychloroquine and asserting divine, geographic (hot temperature), and demographic (being young) protection. Many also perceive the virus as similar to malaria and not considered severe. The implications of these findings for research and policy are discussed.